2013
DOI: 10.1007/978-94-007-6627-3_29
|View full text |Cite
|
Sign up to set email alerts
|

EMG Analysis of Human Inspiratory Muscle Resistance to Fatigue During Exercise

Abstract: The aim of this study was to characterize the pattern of inspiratory muscle fatigue and to assess the resistance to fatigue of the diaphragm (D), parasternal (PS), sternocleidomastoid (SCM), and scalene (SC) muscles. Nine healthy, untrained male subjects participated in this study. Electromyographic activity (EMG) of D, PS, SCM, and SC was recorded during an incremental cycling test to exhaustion (workload of 1.0 W/kg with 0.5 W/kg increments every 5 min). The before-to-after exercise measurements of maximal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
2
12
0
2
Order By: Relevance
“…A decrease in the centroid frequency varied from 5 % to 35 % depending on the muscle; being smaller in case of the diaphragm and chest inspiratory muscles, which points a greater resistance of these muscles to exercise-induced fatigue compared with the accessory muscles of the neck. These data are in line with the majority of other studies (Segizbaeva and Aleksandrova 2014;Janssens et al 2013;Segizbaeva et al 2013).…”
Section: Discussionmentioning
confidence: 60%
“…A decrease in the centroid frequency varied from 5 % to 35 % depending on the muscle; being smaller in case of the diaphragm and chest inspiratory muscles, which points a greater resistance of these muscles to exercise-induced fatigue compared with the accessory muscles of the neck. These data are in line with the majority of other studies (Segizbaeva and Aleksandrova 2014;Janssens et al 2013;Segizbaeva et al 2013).…”
Section: Discussionmentioning
confidence: 60%
“…The major finding of this study was the graphical identification of EMG IP in inspiratory muscles. We believe that this is the first study to identify EMG IP in the scalene and sternocleidomastoid muscles using SEMG under the condition of progressive inspiratory flow velocity produced by increasing the respiratory rate and shortening the inspiratory time using a mask ventilator (2,17,24,29,31,33,36). In addition, the existence of EMG IP infers the existence of EMG AT in inspiratory muscles.…”
Section: Discussionmentioning
confidence: 73%
“…Regarding previous studies of respiratory muscles related to increasing neuromuscular activation against increases in resistive loading, animal experiments found that MUs of respiratory muscles such as fast fibers are recruited in response to tachypnea with an increase in the inspiratory flow (7,8). Meanwhile, there are few studies in humans reporting the existence of respiratory muscle EMG AT (2,17,24,29,33,36).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the intercostal muscles, this indicates that uncontrolled asthma causes the accessory breathing muscles to be recruited. Sternocleidomastoid activity during exhaustive exercise has been assessed by Segizbaeva in 2013 in healthy adult men [94]. Activity of the sternocleidomastoid muscles increased in all subjects of Segizbaeva's study, possibly explaining the increase in reliably measurable patients in both groups.…”
Section: Comparison Of Emg Parameters At Largest Bronchoconstrictionmentioning
confidence: 99%